Differentiation theory and the ontologies of regionalism in Latin America (2017)
In this article, we argue that conventional understandings of regional integration based on neo-functionalism, hitherto often used to describe the diverse projects of Latin American regionalism, are of limited utility in that context. Rather than representing processes of economic or political unification, the various regionalisms could be understood more productively as a reaction to the crisis in legitimacy that social orders in the region have experienced under the conditions of globalized modernity. We then deploy an understanding of regionalism derived from sociological differentiation theory in order to advance this argument.